2015
DOI: 10.1007/s11356-015-4980-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of endocrine-disrupting compounds in the Honghu Lake and East Dongting Lake along the Central Yangtze River, China

Abstract: Lakes along the Yangzte River are very important for inhabitants due to their ecosystem service values. In this study, the level of eight endocrine-disrupting compounds (EDCs) was studied in the Honghu Lake and East Dongting Lake. In each lake, 21 water samples and 21 sediment samples were collected. The total concentrations of eight EDCs in surface water (47.60-419.82 ng L(-1), mean value: 225.65 ng L(-1)) and sediments (202.71-635.36 ng g(-1) dry weight (dw), mean value 371.90 ng g(-1) dw) of Honghu Lake wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The results of a Pearson correlation between TP, TN, NH4-N, nitrate nitrogen (NO3-N), chemical oxygen demand (CODmn), Chla, SD, pH, EC, TDS, F − , water temperature (Tw), biochemical oxygen demand (BOD), P, E, T, and relative humidity (Rh) are shown in Table 4. CODmn, Chl-a, and BOD5 were strongly positively correlated with TP and TN (p < 0.01), which showed that the organic contaminants such as bait was the major pollution source [65]. The concentration of F − would be increased with the pH, EC, and TDS (p < 0.01), while the pH must be more than 7 [53].…”
Section: Statistical Analysis Resultsmentioning
confidence: 94%
“…The results of a Pearson correlation between TP, TN, NH4-N, nitrate nitrogen (NO3-N), chemical oxygen demand (CODmn), Chla, SD, pH, EC, TDS, F − , water temperature (Tw), biochemical oxygen demand (BOD), P, E, T, and relative humidity (Rh) are shown in Table 4. CODmn, Chl-a, and BOD5 were strongly positively correlated with TP and TN (p < 0.01), which showed that the organic contaminants such as bait was the major pollution source [65]. The concentration of F − would be increased with the pH, EC, and TDS (p < 0.01), while the pH must be more than 7 [53].…”
Section: Statistical Analysis Resultsmentioning
confidence: 94%
“…East Dongting Lake, which is connected to the Yangtze River, is the largest lake in the Donging Lake system [17]. It covers the region from approximately 28 • 59" to 29 • 38" and 112 • 43" to 113 • 15" [18], and drains an area of 1900 km 2 , including a water area of 364 km 2 [19]. The location of East Dongting Lake is shown in Figure 1.…”
Section: Study Areamentioning
confidence: 99%
“…One of the most potent of these micropollutants is the synthetic 17-alpha-ethinylestradiol (EE2) that is used in oral contraceptives and hormone replacement therapies, and that is more stable and persistent than the natural estrogen it mimics [1]. EE2 concentrations of 1ng/L and higher have been found in river or lake surface waters [2] in lake sediments [3], and even in groundwater [4].…”
Section: Introductionmentioning
confidence: 99%